Modernization and Westernization: A Never-Ending Discourse in Indonesia (Journal of Governance and Development (JGD), 2011)
Ahead of Indonesian independence in 1945, the discourse on cultural and ideological orientation by Indonesian intellectuals became the foundation for the development of the nation. Sutan Takdir Alisyahbana, one of the Indonesian intellectuals at that time strongly believed that following the pattern of Western culture would lead Indonesia to the status of a developed country. Instead, Sanusi Pane and several other Indonesian intellectuals did not agree with the view of Sutan Takdir Alisyahbana. They considered that cultural values that have long held the nation could be used as a foundation for development of Indonesia. The discourse is then known as the Cultural Polemics. This discourse persists to this day but in a slightly different form, namely the discourse of modernization and Westernization. The progress in science and technology from the outside world created Indonesia a market for western products. The West seemed to be fascinating and the adoption of popular culture from the West, especially the U.S., became part of the lives of many people. The image of the West which was considered to be superior and as a role model became an obsession for many people.